1998
DOI: 10.1038/sj.mp.4000363
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D4 receptor and serotonin transporter promoter in the determination of neonatal temperament

Abstract: Genetic effects on behavior were evaluated at a time in early development when we hypothesized that environmental influences are minimal and least likely to confound associations between temperament and genes. The behavioral effects of two common polymorphisms linked respectively in some, but not all, studies to novelty seeking (dopamine D4 receptor -D4DR) and neuroticism and harm avoidance (serotonin transporter promoter region -STPR) were examined in a group of 81 two-week-old neonates. Neonate temperament w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
117
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(132 citation statements)
references
References 40 publications
15
117
0
Order By: Relevance
“…The current results are consistent with an earlier study 8 in which we demonstrated an interaction between the 5-HTTLPR and DRD4 seven-repeat on Brazelton Orientation scores (perhaps a putative antecedent temperament of adult NS) in 2-week-old neonates. At 2 months of age, these children were again assessed 7 using the Infant Behavioral Questionnaire 17 and a significant interaction between the DRD4 sevenrepeat × 5-HTTLPR promoter region polymorphisms on Negative Emotionality and Distress to Limitations was observed.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…The current results are consistent with an earlier study 8 in which we demonstrated an interaction between the 5-HTTLPR and DRD4 seven-repeat on Brazelton Orientation scores (perhaps a putative antecedent temperament of adult NS) in 2-week-old neonates. At 2 months of age, these children were again assessed 7 using the Infant Behavioral Questionnaire 17 and a significant interaction between the DRD4 sevenrepeat × 5-HTTLPR promoter region polymorphisms on Negative Emotionality and Distress to Limitations was observed.…”
supporting
confidence: 82%
“…[3][4][5] It seems reasonable that as additional genetic information is inventoried for various cohorts, associations between DRD4, 5-HTTLPR and other candidate genes and complex phenotypes will be further clarified. We, [6][7][8] and others, [9][10][11] have begun to examine multiple interactions between common genetic polymorphisms and complex behavioral traits. The catechol O-methyltransferase (COMT) gene contains a common, functional polymorphism in which a val-to-met amino acid substitution markedly reduces enzyme activity to about 20% of wild-type (val) levels.…”
mentioning
confidence: 99%
“…This includes 46 items scored on 4-or 9-point cases, which are reduced to seven summary core clusters, six of which were used (orientation, motor organization, range of state and state regulation, autonomic stability, and reflexes; Ebstein et al 1998). Univariate tests produced only one result that remains significant after correction for seven comparisons for the DRD4 VNTR and orientation (uncorrected p ϭ .00038).…”
Section: Association Of the Drd4 Vntr With Novelty Seekingmentioning
confidence: 99%
“…However, such levels of significance are not appropriate for current studies. Finally, when interactions between polymorphisms of different candidate genes are investigated (e.g., Ebstein et al 1997cEbstein et al , 1998) the number of potential tests rises exponentially, and positive results should be interpreted with great caution.…”
Section: Statistical Considerationsmentioning
confidence: 99%
“…Ebstein and colleagues report a somewhat parallel relationship. 25 In adult subjects without the short form of the 5-HTTLPR, which is supposed to have an influence on anxiety-related traits, 26 they observed a more pronounced effect of long DRD4 alleles. In our cohort, HA and NS subscales are moderately negatively correlated (r −0.20 to −0.44, P Ͻ 0.05).…”
mentioning
confidence: 99%